Biomechanics of hang-time in volleyball spike jumps - Gupta, D.; Jensen, J. L.; Abraham, L. D. (Journal of Biomechanics, 2021)
This study examined whether "hang", an extended period of greatly reduced or zero vertical velocity of the head and trunk created by inter-segmental interactions, would be seen during skilled volleyball player spike jumps. Method